2019
DOI: 10.5152/tud.2018.86836
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Mitrofanoff as bladder draining tool: A single center experience in pediatric patients

Abstract: I n d e x e d i n P u b M e d , W e b o f S c i e n c e a n d S c o p u s Yasemin Yuyucu Karabulut, et al.; The role of COL6A1 and PD-1 expressions in renal cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
1
3
0
2
Order By: Relevance
“…Stomal stenosis and bladder calculi continue to be common complications routinely encountered by physicians after this procedure [5,12]. Renal calculi were observed in our patient as well.…”
Section: Surgical Managementsupporting
confidence: 66%
See 2 more Smart Citations
“…Stomal stenosis and bladder calculi continue to be common complications routinely encountered by physicians after this procedure [5,12]. Renal calculi were observed in our patient as well.…”
Section: Surgical Managementsupporting
confidence: 66%
“…To achieve suitable continence rates, concomitant bladder augmentation is usually performed alongside a Mitrofanoff procedure, especially when there are underlying congenital bladder anomalies; a study at a tertiary care hospital in Pakistan reported successful outcomes [6]. However, complications such as UTI and bladder calculus formation continue to occur even with this approach, probably due to concomitant intestinal augmentation and lack of clean catheterization techniques [5].…”
Section: Surgical Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Он предложил использовать аппендикс в качестве естественной трубчатой структуры, посредством которой можно соединять мочевой пузырь и поверхность кожи. Мобилизованный на сосудах собственной брыжейки червеобразный отросток одним концом анастомозируют с мочевым пузырем, а другой выводят на кожу с формированием небольшого губовидного свища [32]. В дальнейшем катетеризацию мочевого пузыря осуществляют через аппендикостому, которая (при соблюдении рекомендованной техники) обеспечивает континенцию мочи.…”
unclassified
“…Если тщательно рассмотреть риски и достоинства каждого метода на этапе дооперационного планирования, можно добиться неплохих результатов. В большинстве исследований авторы указывают на то, что в соответствующих клинических ситу-ациях мочевая континенция при создании катетеризируемых аппендиковезикостом была достигнута более чем в 90 % случаев [32,40,42].…”
unclassified